2022
DOI: 10.1017/s1368980022000696
|View full text |Cite
|
Sign up to set email alerts
|

Individual and interpersonal factors affecting dietary intake of community-dwelling older adults during the COVID-19 pandemic

Abstract: Objective: As older adults are at higher risk for severe illness and mortality from SARS-CoV-2 infection, social distancing has been a primary means of mitigating risk. However, this lifestyle change may impact eating habits and food choices. The aim of this study was to explore individual and interpersonal factors affecting the eating behaviours and dietary intake of community-dwelling older adults during the COVID-19 pandemic. Design: Semi-structured individual interviews were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…An active role in the community is a strong indicator of social support and amplifies integration into society. In a few studies, social factors such as informal networks have been identified to have an influence on food-related behaviours [39][40][41]. If we assume that active participation in a club helps to avoid social isolation, our findings are in line with previous studies.…”
Section: Social Behaviour Personality Traits and Political Preferencessupporting
confidence: 90%
“…An active role in the community is a strong indicator of social support and amplifies integration into society. In a few studies, social factors such as informal networks have been identified to have an influence on food-related behaviours [39][40][41]. If we assume that active participation in a club helps to avoid social isolation, our findings are in line with previous studies.…”
Section: Social Behaviour Personality Traits and Political Preferencessupporting
confidence: 90%
“…This is a unique finding as a previous study reported the beneficial association from adults who cooked at home more during the pandemic [ 32 ]. Another study with older adults reported cooking as a form of entertainment and a stress reliever from the pandemic [ 33 ]. From the present study, the lack of socializing may have further increased care-partner stress as social isolation has been shown to be associated with nutrition risk for older adults [ 34 ].…”
Section: Discussionmentioning
confidence: 99%